New dimensions of monetary management - Mody, R. J. (Delhi : Macmillan Co. of India, 1974)
This book analyses monetary management in India in the context of the objectives of price stability. A basic monetary issue analysed in the book is the ability of the Indian monetary authority to freely carry out its task of economic stabilization.
Includes indexes.
Bibliography: p. [117]-120.
usc 20/09/18
Loans
Keywords: Money; Monetary policy; Credit; India